Transformation and dynamic visualization of images from computer through an FPGA in a matrix of LED - Edwar Jacinto Gómez; Fernando Martínez Santa; Holman Montiel Ariza (Universitas Ahmad Dahlan, 2019)
This article shows the implementation of a system that uses a graphic interface to load a digital image into a programmable logic device, which is stored in its internal RAM memory and is responsible for visualizing it in a matrix of RGB LEDs, so that This way, the LEDs show an equivalent to the image that was sent from the PC, conserving an aspect ratio and respecting as much as possible the color of the original image. To carry out this task, a Matlab script was designed to load the image, convert and format the data, which are transmitted to the FPGA using the RS232 protocol. The FPGA is in charge of receiving them, storing them and generating all the signals of control and synchronization of the system including the control of the PWM signals necessary to conserve the brightness of each one of the LEDs. This system allows the visualization of static images in standard formats and, in addition, thanks to the flexibility of the hardware used, it allows the visualization of moving images type GIF.